Lecturer Leadership in Influencing Learning Class Members Faced with the Covid-19 Pandemic Conditions - Tatar Bonar Silitonga (International Journal of Science and Society, 2021)
This study is intended to analyze the leadership of lecturers in influencing members of the Civic Education learning class faced with the Covid-19 Pandemic. The discussion focused on controlling tactics used by lecturers in-class activities, including the initial stage, the running stage, to the final step. Qualitative methods are used to discuss the problem, and the data analysis approach is carried out using descriptive techniques. Data was collected using interviews with selected lecturers, observations, and literature studies. The process is complemented by the role of the researcher as the main instrument. The data results show that the influence tactics used by lecturers in their leadership are adjusted to existing conditions, including the initial stage, the running stage, and the final stage referring to the dynamics of the Covid-19 pandemic condition.